2013
DOI: 10.1097/mib.0b013e318296ae5a
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy and Methodological Challenges of Psychotherapy for Adults with Inflammatory Bowel Disease

Abstract: Adults with inflammatory bowel disease (IBD) are at a greater risk of anxiety and depression and impaired quality of life (QoL) compared with healthy controls and other chronic physical illness groups. Consequently, the development and evaluation of well-defined and theoretically robust psychotherapeutic interventions for adults with IBD are desirable. To date, interventions have, for the most part, used multiple cross-theoretical approaches. Published reviews are heterogeneous in terms both of categorization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
69
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(83 citation statements)
references
References 46 publications
4
69
1
3
Order By: Relevance
“…adolescent somatic symptoms, parent irrational cognitions, and protective responses to pain/IBD symptoms). These findings are consistent with face-toface/group-based interventions targeting GI symptoms and mental health (see reviews: Zijdenbos et al [32], Timmer et al [33], and Knowles et al [15]), in that it can be argued that individuals who experience mental distress along with their physical health condition are likely to benefit from a focused psychological intervention. It is, however, too early to identify if targeted eHealth psychological interventions may be more beneficial for different illness cohorts (i.e.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…adolescent somatic symptoms, parent irrational cognitions, and protective responses to pain/IBD symptoms). These findings are consistent with face-toface/group-based interventions targeting GI symptoms and mental health (see reviews: Zijdenbos et al [32], Timmer et al [33], and Knowles et al [15]), in that it can be argued that individuals who experience mental distress along with their physical health condition are likely to benefit from a focused psychological intervention. It is, however, too early to identify if targeted eHealth psychological interventions may be more beneficial for different illness cohorts (i.e.…”
Section: Discussionsupporting
confidence: 68%
“…stress, disease status, medication type and changes). It also evaluates differences between completers and non-completers Adapted from Knowles et al [15]. Hunt et al [18] First IBS online study, involving patient-therapist communication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors combined stress management, psychodynamic psychotherapy and cognitive behaviour therapy (CBT) studies as "psychotherapy" in the meta-analysis, therefore any differential efficacy between these theoretically distinct approaches could not be evaluated. When considered independently, a more recent review found promising evidence that CBT improved mental health in patients with IBD, both immediately following the intervention and at 6 months follow up (Knowles et al, 2013). …”
Section: Accepted Manuscriptmentioning
confidence: 96%
“…22 Responding to the links between psychological distress, IBD and QoL, several psychological strategies have been trialed, including stress management, psychodynamic and cognitivebehavioral interventions; for reviews of this literature, see Refs. 23-26. In the most recent systematic review of psychological interventions in IBD, Knowles et al 27 concluded that while some interventions, particularly cognitive-behavioral therapy, have provided evidence for improving psychological well-being, there is limited evidence for their beneficial impact on QoL or disease activity. Knowles et al 27 argued that future psychologically oriented IBD interventional trials should address previous methodological limitations (e.g., lacking control groups, accounting for dropouts, and missing data) and also explore other potentially useful treatment modalities, particularly those involving mindfulness.…”
mentioning
confidence: 98%